Growth, physiological responses, and enzymatic activities in immature stages of five Hevea brasiliensis willd clones under water stress - Mohd Zan, Noorliana (2013)
The effects of water stress treatment through variation in the duration of stress applied (i.e 7, 14, 21, 28 days) on growth and physiological responses of immature Hevea brasiliensis clones were investigated under glasshouse condition in comparison with a unstressed. 5 clones were found to have similar responses under a well-watered control condition. Water stress significantly (p≤0.05) reduces soil moisture, biomass partitioning, specific leaf area, leaf area ratio and leaf weight ratio. Similarly, gas exchange in stressed Hevea clones had a significant effect on the net photosynthesis,stomata conductance, leaf water potential and transpiration rate. In contrast, the increase of water stress duration increased the root shoot ratio (R:S) and water use efficiency (WUE). On the other hand, in terms of clones, RRIM 3001, RRIM 2002 and RRIM 929 exhibited characteristics of maintained photosynthesis, stomata conductance, leaf water potential under water deficit by maintaining high plant water status through prompt stomata regulation (high water use efficiency), as compared to RRIM 2008 and RRIM 2014 that were sensitive to water deficit. Additionally, significant linear relationship were found between leaf water potential,stomata conductance and net photosynthesis. A significant relationship on net photosynthesis and leaf water potential was also obtained. These relationships show an ability to adapt and maintain root to shoot communication under a water stress condition that support the gas exchange findings. Water stress of Hevea plants could decrease the level of chlorophyll a, chlorophyll b, total chlorophyll content and maximum quantum efficiency of photosystem II (PS II). However, in this study chlorophyll a, chlorophyll b and total chlorophyll content were not significantly affected by water stress. The decrease of maximum quantum efficiency of photosystem II was due to the impairment of net photosynthesis which limits the availability of CO2 concentration. Moreover,water stress had rapidly increased biochemical constituents, such as ascorbate peroxidase (APX), guaiacol peroxidase (GPOX) and catalase (CAT) which exhibited progressive scavenge of reactive oxygen species (ROS) formation to prevent photo oxidation or oxidative stress. On the other hand, RRIM 3001 had the ability to maintain carbon dioxide (CO2) concentration and better scavenging defense mechanism for ROS as compared to RRIM 2014 under stressed condition. Overall results revealed that RRIM 3001 clone had the most similar water stress tolerance characteristic and suggest that water stress applied to immature Hevea clones will gradually affect their growth,physiology and trigger enzymatic antioxidants to overcome formation of ROS molecules.